Social Responsibilities of the Businessman. - Bowen, Howard R. (University of Iowa faculty connections., 2013)
Corporate social responsibility (CSR) expresses a fundamental morality in the way a company behaves toward society. It follows ethical behavior toward stakeholders and recognizes the spirit of the legal and regulatory environment. The idea of CSR gained momentum in the late 1950s and 1960s with the expansion of large conglomerate corporations and became a popular subject in the 1980s with R. Edward Freeman's Strategic Management: A Stakeholder Approach and the many key works of Archie B. Carroll, Peter F. Drucker, and others. In the wake of the financial crisis of 2008-2010, CSR ha.